Mindfulness-based family psychoeducation intervention for caregivers of young adults with first-episode psychosis: results at 9-month follow-up - Zhang, Zoe Jiwen; Lo, Herman Hay Ming; Ho, Wing Chung; Lau, Elsa Ngar Sze; Ng, Siu Man; Mak, Winnie W. S.; Wong, Samuel Yeung Shan; Hung, Karen S. Y.; Lai, Iris Yuen Shan; Lo, Cola Siu Lin; Wong, Jessica Oi Yin; Lui, Simon S. Y.; et al. (Frontiers in Psychiatry, 2024)
Objectives To investigate the effects of a mindfulness-based family psychoeducation (MBFPE) intervention on caregivers and the young adults with first-episode psychosis in mental health care. Methods Sixty-five caregivers were randomly assigned to the MBFPE program (n = 33) or an ordinary family psychoeducation (FPE) program (n = 32). Eighteen young adults in recovery (YAIR) also participated in the study. All of the participants completed the assessments before participating in the intervention (T1), after the intervention (T2), and at 9-month follow-up (T3). Results Intention-to-treat analyses were conducted. The caregivers reported a significant and large effect size on positive caregiving experiences based on a Time × Group analysis (g = 0.862, p = 0.006). Among the YAIR participants, between-group differences were significant in their perceptions of caregivers’ expressed emotions, including large effect sizes of perceived criticism (g = 1.396, p = 0.049) and hostility (g = 1.444, p = 0.043). Caregiver demographics, including age, education level, socioeconomic status, and number of family members, were found to moderate the effect sizes of the variables studied. Conclusion This study provides evidence of the effects of MBFPE programs on the outcomes of caregivers and the young adults with first-episode psychosis in their care. Specifically, the MBFPE program in this study played a greater role in promoting positive caregiving experiences and changing caregivers’ expressed emotions, especially their expressed criticism of YAIR, compared with the regular FPE program. Therefore, the application of mindfulness training to promote family care and YAIR recovery should be encouraged. Clinical trial registration ClinicalTrials.gov, identifier NCT03688009.